Criminogenic factors of child protection crime convicts in class IIB pacitan detention center - Dicky Arief Endriansah; Mulyani Rahayu (Journal of Law Science, 2024)
This study explores the criminogenic factors influencing inmates convicted of child protection crimes at the Class IIB State Detention Center (Rutan) in Pacitan. The research is grounded in the alarming rate of child protection cases in Indonesia, with Pacitan ranking second in the number of such cases within the facility. The primary aim is to identify both internal and external factors that drive inmates to commit crimes against children, as well as to assess the effectiveness of the rehabilitation programs implemented. This qualitative descriptive study employs data collection methods including in-depth interviews, observation, and document analysis. The research subjects consist of five inmates aged 19–25 and two correctional officers. The findings reveal several dominant criminogenic factors, such as lack of self-control, social environment influence, antisocial personality traits, alcohol abuse, and family conflict. Rehabilitation programs at the detention center, which include religious activities and vocational training, have not yet fully addressed the specific needs of inmates. The study recommends the adoption of the Risk-Need-Responsivity (RNR) model to reduce recidivism and better prepare inmates for reintegration into society. These findings are expected to inform policymakers in enhancing inmate rehabilitation systems, particularly for child-related offenses.